Optimasi Komposisi Pakan Ayam Broiler Sesuai Standarisasi Kebutuhan Nutrisi Menggunakan Algoritma Genetika - Anas Abiem Bahar (Jurnal Teknologi Informasi dan Terapan, 2019)
Quality of brioiler fedd impact on meat quality produced. If feeding broiler unstandarized so broiler will be non optimal condition such as lack of appetite an energy, susceptible to disease. Even consequences can lead to death on the broiler. To minimize the mortality in broiler then used to genetic algorithm as combination of chicken feed with an optimal output. The advantage of using a genetic algorithm is seen from its ability to find a good solution. The advantages of genetic algorithms when compared to other algorithms are the less mathematical calculation process. This algorithm will look for solutions without regard to processes related to problems that are solved directly. This study will design the optimization of the best combination of feed in Broiler chickens according to the appropriate price using the genetic algorithm method. From the results of research conducted obtained at the best generation to generation 17 with the best fitness value is 0.0792 and the smallest fitness value is 0.0412 with average fitness obtained is 0.05829.